Comparative Study on Production Efficiency of Two Strains of Brown and White Egg Laying Hens in Kuwait - Ragheb , G.; Al-Nasser, A.E.; Abdullah, F.K.; Al-Bahouh, M.E.; Al-Saffar, A.; Al-Khalifa, H.; Mashaly, M.M. (International Journal of Poultry Science, 2013)
The high nutritional value of eggs makes them an important part of the normal diet of people in general and specifically in Kuwait. The majority of egg consumption in Kuwait and the Gulf area is of the white egg type. However, it is known that the majority consumption in European countries and in the Middle East is of the brown egg type. This could be due to high quality of brown eggs including shell thickness. Therefore, the current research was conducted to assess the quality of brown eggs as compared to white eggs for two laying hen strains under local conditions. Furthermore, comparison between production efficiency of brown and white laying hens was conducted. Hy-line brown and white laying hen strains were used in the current study. During the laying period (22-69 weeks of age), percent egg production, egg weight, egg mass, feed consumption and feed efficiency were determined every four weeks. Shell weight, thickness, yolk and albumen weight and percentage and Haugh unit were determined at different laying periods for both brown and white eggs. It was found that egg production, egg weight and egg mass of the brown hens were significantly (P0.05) in the feed consumption between brown and white hens. However, feed efficiency was significantly (P